Meningkatkan Kemampuan Memahami Bacaan Al-Quran melalui Penerapan Metode Mind MAP pada Siswa Pendidikan Anak Usia Dini Qur’an An-Najah Bogor Jawa Barat - Rohim, Abd (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
PAUDQu An-Najah is an educational institution for pre-primary school children. This research aims to analyze improving the ability to understand reading using the mind map method in early childhood at PAUDQu An-Najah Bogor. The method used in this research is the Participatory Action Research (PAR) method, namely research that actively involves all relevant parties (Stakeholders) in reviewing ongoing actions (where their own experiences are the problem) in order to make changes and improvements to better direction. With characteristics, problem, solution, transformation, and model.. From the results of action research through the application of the mind map method, student learning outcomes increased from before and after applying the mind map method by 35.7 percent, so that in an effort to improve student understanding learning outcomes towards the ability to read the Qur'an, it is necessary to apply the mind map method in learning to read the Qur'an regularly and continuously